Experimental study on the performance of household electric cooking stoves: Locally made versus imported technologies - Molla Asmare Alemu; Muluken Zegeye. Getie (Energy Reports, 2024)
Biomass combustion produces air pollutants, causing high mortality rates, while electric cooking, which is efficient and eco-friendly, reduces mortality and maximizes socio-economic and ecological benefits. Thus, the primary purpose of this study is to compare the performance of domestic and imported household electric hotplate stoves via experimental investigation. For the study, 20 households have been purposively selected in Bahir Dar, Ethiopia from low- and middle-income groups. Following that, the researchers trained the participants and enumerators to record the energy consumption and time taken for each cooking event. The experiments have been conducted using medium-sized domestic and imported electric hotplate stoves for 15 days each. Digital energy meters have been used to record the daily cooking energy demand. Participants record the daily data using the developed Excel spreadsheet. Accordingly, the study disclosed that the average daily cooking energy consumption per household for locally-made and imported electric cookstoves is 3.55 kWh and 2.81 kWh, respectively. The result also reveals that local electric stoves are subjected to inferior efficiency and higher heat losses. On the other hand, the analysis of the average time required to cook a meal revealed that cooking with imported cookstoves took slightly longer than cooking with locally-made cookstoves. This is because as there is no power-control mechanism, locally-made electric stoves usually work at maximum power rate and cook faster than imported ones. Moreover, the average monthly energy expense per household using these stoves in their respective ways were $3.90 (213.33ETB), and $3.1(169.86ETB), suggesting that locally manufactured stoves have higher energy cost bills. An independent T-test results revealed a significant difference (p < 0.001) between the two types of stoves. However, most households use locally made electric cook stoves due to their low prices, easy maintenance, and low understanding of stove efficiency. Hence, further investigation is needed to improve the efficiency and standardization of local electric cook stoves and increase the supply chain of imported electric appliances.